2023
DOI: 10.1073/pnas.2303358120
|View full text |Cite
|
Sign up to set email alerts
|

An interchangeable prion-like domain is required for Ty1 retrotransposition

Abstract: Retrotransposons and retroviruses shape genome evolution and can negatively impact genome function. Saccharomyces cerevisiae and its close relatives harbor several families of LTR-retrotransposons, the most abundant being Ty1 in several laboratory strains. The cytosolic foci that nucleate Ty1 virus-like particle (VLP) assembly are not well understood. These foci, termed retrosomes or T-bodies, contain Ty1 Gag and likely Gag-Pol and the Ty1 mRNA destined for reverse transcription. Here, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Alternatively, they could be subject to degradation in a pathway similar to misfolded proteins. A recent study also identified a prion-like domain in the Ty1 Gag protein, which is responsible for VLP assembly and thus appears implicated in phase separation processes ( 70 ). Our data suggest that VLPs interact with PQC components based on three lines of results.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, they could be subject to degradation in a pathway similar to misfolded proteins. A recent study also identified a prion-like domain in the Ty1 Gag protein, which is responsible for VLP assembly and thus appears implicated in phase separation processes ( 70 ). Our data suggest that VLPs interact with PQC components based on three lines of results.…”
Section: Discussionmentioning
confidence: 99%